Development of a self-administered menu management and pricing framework for small and micro restaurant establishments - Lai, Jack Hao Bin (2022)
Food service businesses in Malaysia recorded an average gross output growth of 11.7% annually, amounting to RM 82.8 billion in 2017. The number of food service businesses increased about 5.1% annually from 130,570 to 167,490 establishments in this recent decade. However, unexpected circumstances, such as the COVID-19 pandemic, have disrupted many economical activities, resulting in many failing restaurants. This has created a highly competitive environment for the restaurant operators. Small and micro restaurant establishments are unquestionably at a disadvantage in terms of the business environment, expertise, capabilities, and resources compared to established franchise and chained restaurants. As the saying goes, a profitable restaurant is a successful restaurant. The mismanagement of menu costing and pricing has put many small and micro restaurant establishments at high risk of failure. Existing menu management approaches, such as menu analysis and revenue management, are deemed impractical to be implemented in small and micro restaurant establishments due to their limited access to resources and high learning curve. With that, the current study aimed to develop a practical framework that can help small and micro restaurant decision makers to manage their menu using a pragmatic qualitative approach. The current study adapted a constructive approach to identify critical aspects to achieve a profitable menu from the practical perspectives. This study also comprehensively reviewed the practicality of existing menu management concepts as well as the potential to integrate several prominent theoretical concepts to form a dynamic framework that can holistically assess menu item specifications. In particular, this study focused on simplifying and adapting the existing menu analysis and revenue management concepts to the current work practices of small and micro restaurant establishments. The constructive research approach split this study into four key phases. Firstly, the preparatory phase involved conducting interviews with medium, small and micro restaurant practitioners to identify the key activities of menu management. The findings revealed the significance of considering internal and external conditions of both people and environmental aspects. Following that, the development phase focused on the development of a dynamic practical framework based on the key activities of menu management according to the varying skills and resource accessibility of restaurant decision makers. Meanwhile, the fieldwork phase implemented the developed framework in eight restaurants to determine the ideal implementation conditions. The findings revealed that knowledge of restaurant decision makers and the degree of control over menu development and pricing restrict the effectiveness of the self-administered framework. Finally, the theorising phase revealed that the developed framework was not feasible for daily routine operations, but more suited for strategic planning, considering the roles and responsibilities of small and micro restaurant decision makers in various non-management tasks. In essence, the MMP framework components were developed through embedding practical menu analysis and revenue management concepts with considerations of the small and micro restaurant’s business environment. Most importantly, this study demonstrated the significance of the developed framework in guiding restaurant decision makers to devise actionable decisions for their menu items. The development of a practical framework on menu management and pricing for small and micro restaurant establishments in this study was expected to benefit the restaurant industry and lower the risk of restaurant failure as well as to support the sustainability of small and micro restaurant businesses.